FORMULATION AND EVALUATION OF IVABRADINE HYDROCHLORIDE LOADED TRANSFERSOMAL GEL FOR TRANSDERMAL DELIVERY - CHAURASIA, GITA; LARIYA, NARENDRA (International Journal of Applied Pharmaceutics, 2020)
Objective: Aim of this study was to develop the topical delivery containing ivabradine hydrochloride (IVH) loaded transpersonal gel for symptomatic treatment of chronic stable angina pectoris in coronary artery disease. Methods: Different hydrophilic-lipophilic balance (HLB) values of surfactants-tween-80, span-80 and sodium deoxycholate (SDC) were investigated to prepare transfersomes (TFs)respectively, with different concentration of soya phosphatidylcholine and 10% v/v ethanol in phosphate buffer solution (pH 6.8) by conventional rotary evaporation sonication method. The prepared formulations were evaluated for percentage entrapment efficiency (%EE), deformability index (DI), turbidity, vesicle shape and size, in vitro drug release study and stability. SEM was done on selected formulation F8 and liposome formulation (LF). Gel was prepared by using carbopol-940 as a gelling agent with propylene glycol, polyethylene glycol solution as permeation enhancer by 32 factorial design optimization methods. The developed gel was evaluated for pH, viscosity, drug content, ex-vivo permeation studies and stability studies of TFs-gel. This was compared with LF-gel prepared by same procedure. Results: Maximum % EE (78.4±0.94), suitable vesicular size (128.6 nm) and maximum DI (34.9±1.9) was found in TFs-TW-80 and selected for gel development. In vitro drug release data from TFs-TW-80, plain drug solution and liposomal formulation (LF) revealed that % cumulative drug released in TFs-TW-80 was found maximum (89.5±0.12 %) in 20 min than others. It was 2.1 times higher than LF and 3.3 times higher than the plain drug. SEM study showed spherical shape of vesicles. The drug contents in the TFs and LF gels were found to be 92 to 95%w/w. Partition coefficient for TFs-loaded gel was 1.04±0.03. Ex vivo permeation study from hairless rat skin showed that permeation of drug is described by firstly first-order kinetics than zero-order kinetics. The drug released from TFs-gel was found to be 1.7 times higher than LF-gel and about 1.9 times higher than plain drug. Flux from TFs-gel was 2.04 times greater than LF-gel and 3.28 times more than plan drug. Stability studies indicated that suitable storage condition for developed gel was temperature 25 °C or less, where the pH, potency and therapeutic efficacy of formulations remain constant. Conclusion: Thus, transdermal route has become one of the most successful and innovative focus for research in drug delivery of IVH loaded TFs-TW-80 to increase stability and bioavailability.